Navigating the shadows: The impact of mindfulness, cognitive fusion, and coping strategies on psychological distress among mental health workers in Timor Leste - Gaspar Quintao; Noviyanti Carla Tilman Leite; Tze, Nicholas Ping Pang; Boon, Eugene Yau Koh; Jhia, Mae Woo; Marina Abdul Rahman Sabri; Kah, Mun Wan; Noor Melissa Noor Hadi; Ming, Gui Tan; Assis Kamu; Chong, Mun Ho (Springer Nature, 2025)
A cross-sectional study design was employed, involving a convenience sample of 37 mental health workers from PRADET and the national referral hospital in Dili. Mindfulness was assessed using the Toronto Mindfulness Questionnaire (TMQ), psychological flexibility using the Acceptance and Action Questionnaire (AAQ-II), cognitive fusion was measured using the Cognitive Fusion Questionnaire (CFQ), and coping strategies were evaluated using the DBT-Ways of Coping Checklist (DBT-WCCL). Depression, anxiety, and stress were measured using the Depression Anxiety Stress Scales (DASS-21). All scales were using English validated versions. Descriptive statistics, Pearson correlation coefficients, and multiple regression analyses were used to analyze the data. Significant positive correlations were found between Depression and Anxiety (Spearman’s rho = 0.649, p < 0.001), and between Depression and Stress (Spearman’s rho = 0.753, p < 0.001). Depression was also significantly correlated with Cognitive Fusion (Spearman’s rho = 0.445, p = 0.006) and Blaming Others (Spearman’s rho = 0.422, p = 0.009), and negatively correlated with Coping Strategies (Skills Use) (Spearman’s rho =– 0.341, p = 0.039). Anxiety and Stress were highly correlated (Spearman’s rho = 0.855, p < 0.001), and both were significantly associated with Cognitive Fusion, General Dysfunctional Coping, and Blaming Others. Mindfulness (De-Centering) showed a strong positive correlation with Mindfulness (Curiosity) (Spearman’s rho = 0.770, p < 0.001), and was also weakly associated with General Dysfunctional Coping (Spearman’s rho = 0.343, p = 0.038). Overall, the results suggest that higher levels of depression, anxiety, and stress are linked to greater cognitive fusion and dysfunctional coping, while effective coping skills are negatively associated with depression. The findings highlight the critical roles of cognitive fusion and coping strategies in predicting psychological distress among mental health workers in Timor Leste. Cognitive fusion and dysfunctional coping strategies were associated with higher levels of depression, anxiety, and stress. Adaptive coping strategies, such as skills use, were linked to lower levels of depression. Given the high risk of vicarious trauma, compassion fatigue, and secondary traumatic stress disorder in this population, targeted interventions promoting mindfulness and adaptive coping skills are essential. Addressing these factors can enhance resilience and well-being among mental health professionals, ultimately improving the quality of care provided to their clients.